Lease Contract Practices in Fishing Pond Rentals from the Perspective of Islamic Law - Wicaxsono, Ilham Agung; Wargo; Kurniawan (Zabags International Journal of Islamic Studies, 2025)
This study explores the leasing mechanism of fishing ponds from an Islamic legal perspective, focusing on the practice at Pojok Ikan Jambi as a case study. The background of this research is rooted in the importance of ensuring that economic transactions, particularly those involving ijarah (leasing), align with Sharia principles to guarantee fairness, transparency, and mutual benefit. The primary objective is to examine the operational system of pond rentals and assess the validity of the contract structure used within the framework of Islamic law. Utilizing a qualitative case study approach, data were collected through direct observation, interviews with the pond owner and customers, and documentation analysis. The findings reveal that the leasing system at Pojok Ikan Jambi operates on a time-based access model tied to a prior fish purchase, forming a composite contract structure (al-uqud al-murakkabah). Despite the informal verbal nature of the agreement, the practice meets essential criteria of Islamic leasing, including mutual consent and benefit clarity. This article contributes to the understanding of how informal community-based business models can ethically implement Islamic economic principles. The implications encourage Sharia-based contract literacy and contextually grounded policy support for micro-enterprises operating under similar informal frameworks.